Cervical artificial disc replacement versus fusion in the cervical spine: a systematic review comparing long-term follow-up results from two FDA trials - Mummaneni, Praveen V; Amin, Beejal Y; Wu, Jau-Ching; Brodt, Erika D; Dettori, Joseph R; Sasso, Rick C (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Clinical question: Does single-level unconstrained, semiconstrained, or fully constrained cervical artificial disc replacement (C-ADR) improve health outcomes compared with single-level anterior cervical discectomy and fusion (ACDF) in the long-term?Methods: A systematic review was undertaken for articles published up to October 2011. Electronic databases and reference lists of key articles were searched to identify US Food and Drug Administration (FDA) studies reporting long-term (≥ 48 months) follow-up results of C-ADR compared with ACDF. Non-FDA trials and FDA trials reporting outcomes at short-term or mid-term follow-up periods were excluded. Two independent reviewers assessed the strength of evidence using the GRADE criteria and disagreements were resolved by consensus.Results: Two FDA trials reporting outcomes following C-ADR (Bryan disc, Prestige disc) versus ACDF at follow-up periods of 48 months and 60 months were found (follow-up rates are 68.7% [318/463] and 50.1% [271/541], respectively). Patients in the C-ADR group showed a higher rate of overall success, greater improvements in Neck Disability Index, neck and arm pain scores, and SF-36 PhysicalComponent Scores at long-term follow-up compared with those in the ACDF group. The rate of adjacent segment disease was less in the C-ADR group versus the ACDF group at 60 months (2.9% vs 4.9%). Normal segmental motion was maintained in the C-ADR group. Furthermore, rates of revision and supplemental fixation surgical procedures were lower in the arthroplasty group.Conclusions: C-ADR is a viable treatment option for cervical herniated disc/spondylosis with radiculopathy resulting in improved clinical outcomes, maintenance of normal segmental motion, and low rates of subsequent surgical procedures at 4 to 5 years follow-up. More studies with long-term follow-up are warranted.